The mitigation of risk in resilient supply chains - Martin Christopher (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2018)
This paper examines the sources of supply chain risk and suggests ways in which higher levels of resilience can be achieved. Recent years have seen a significant increase in the risk of supply chain disruption and the need for resilience across the supply/demand network has become imperative. The paper discusses the focus on agility and flexibility required to achieve higher resilience, which in turn will require new ways of working across organisational boundaries.
Keywords: 330